Faktor-Faktor Yang Mempengaruhi Kemiskinan Di Jawa Tengah Periode 2002-2021 Analisis Data Time Series (International Forum of Researchers and Lecturers, 2023)
Poverty is a condition where people are unable to meet their basic needs. Poverty can be said to be a fairly complicated matter that is being experienced by various countries in the world, especially a developing country like Indonesia. Poverty can be used as a measuring tool for socio-economic conditions in assessing the success of development carried out by the government in an area. Various impacts that can arise from the increase or lack of handling of the poverty rate include a decrease in the level of social welfare, an increase in the crime rate, a decrease in the level of public health, a decrease in the quality of education and there are still many social problems that will arise as a result of this poverty. The poverty rate can be influenced by various factors including GRDP (Gross Regional Domestic Product), HDI (Human Development Index) and TPT (Open Unemployment Rate). This study examines the effect of GRDP, HDI and TPT on poverty in Central Java Province in 2002-2021. The purpose of this study is expected to be able to analyze how and how much influence GRDP, HDI and TPT have on poverty in Central Java Province, so that it is hoped that later this can be used as a basis for determining policies to overcome poverty in Central Java Province. The data used in this study is secondary data obtained through the Central Bureau of Statistics (BPS). The method of analysis in this study is the time series data analysis method of estimating the ECM model with the help of Eviews 10. The results show that the relationship between GRDP, HDI and TPT has a significant effect on the poverty rate in Central Java Province.